Hyphal tip extension in Aspergillus nidulans requires the manA gene, which encodes phosphomannose isomerase. - Smith, D J (1994)
A strain of Aspergillus nidulans carrying a temperature-sensitive mutation in the manA gene produces cell walls depleted of D-mannose and forms hyphal tip balloons at the restrictive temperature (B.P. Valentine and B.W. Bainbridge, J. Gen. Microbiol. 109:155-168, 1978). We have isolated and characterized the manA gene and physically located it between 3.5 and 5.5 kb centromere distal of the riboB locus on chromosome VIII. The manA gene contains four introns and encodes a 50.6-kDa protein which has significant sequence identity to type I phosphomannose isomerase proteins from other eukaryotes. We have constructed by integrative transformation a null mutation in the manA gene which can only be maintained in a heterokaryotic strain with wild-type manA+ nuclei. Thus, a manA null mutation is lethal in A. nidulans. The phenotype of the mutation was analyzed in germinating conidia. Such conidia are able to commence germination but swell abnormally, sometimes producing a misshapen germ tube, before growth ceases. The reason for the lethality is probably the lack of synthesis of mannose-containing cell wall polymers that must be required for normal cell wall development in growing hyphae.